217k views
25 votes
How do you solve -5 ( -6 - 3x) + 8 = 83

User Andreask
by
5.5k points

1 Answer

6 votes

Answer:

x=3

Explanation:

-5(-6-3x)+8=83

Distribute the -5 to both terms in the parentheses by multiplication, multiply the -5 by the -6 and the -3x.

30+15x+8=83

Add like terms, add the 30 and the 8.

38+15x=83

Subtract 38 from both sides to isolate the x on the left side.

15x=45

Divide by 15 on both sides to solve for x.

x=3

User Krsi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.